2022
DOI: 10.1021/acsomega.2c01153
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Reusable, Cell Uniformly Distributed Membrane Filtration Device for Separation of Circulating Tumor Cells

Abstract: Isolation of circulating tumor cells (CTCs) is of great significance for the diagnosis, prognosis, and treatment of metastatic cancer. Among CTC capture methods independent of antibodies, membrane filtration-based methods have the advantages of simplicity, rapidity, and high throughput but usually have problems such as clogging, high pressure drop, and impaired cell viability. In this study, we designed and tested a reusable device that used horizontal rotor and fluid-assisted separation to capture CTCs by cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, microfilters that isolate cells based on their size tend to cause cell clogging, reducing cell recovery and purity. To solve this problem, Han et al designed a membrane filtration device with a horizontal rotor for even cell distribution, improving cells isolation in centrifuges, as shown in Figure 6 A [ 101 ]. Li et al designed a windmill-like uniform touch (SU-8 film) pore array, as shown in Figure 6 B.…”
Section: Label-independent Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, microfilters that isolate cells based on their size tend to cause cell clogging, reducing cell recovery and purity. To solve this problem, Han et al designed a membrane filtration device with a horizontal rotor for even cell distribution, improving cells isolation in centrifuges, as shown in Figure 6 A [ 101 ]. Li et al designed a windmill-like uniform touch (SU-8 film) pore array, as shown in Figure 6 B.…”
Section: Label-independent Methodsmentioning
confidence: 99%
“…15, x FOR PEERREVIEW 12 of 32 shown in Figure 6A[101]. Li et al designed a windmill-like uniform touch (SU-8 film) pore array, as shown in Figure6B.…”
mentioning
confidence: 99%
“…However, challenges such as low CTC recovery and clogging of the porous filter arise due to high filtration pressure and elevated hematocrit levels. 60 It is worth noting that the future of sizebased isolation can serve as an accessible and preliminary method for CTC isolation. By sidestepping complex channel designs, they may enable rapid CTC isolation and enumeration within 10 min, while maintaining clinically acceptable sensitivity and specificity.…”
Section: Size Based Ctc Isolationmentioning
confidence: 99%
“…The physical strategies for CTC isolation can be categorized into two main approaches: active isolation and passive isolation. Passive isolation techniques rely on specialized channel designs to separate CTCs based on their intrinsic properties, such as size, 60 deformability, 62 hydrodynamic features, 64 and viscoelastic migration 65 . On the other hand, active isolation involves the use of external fields to manipulate cancer cells, such as light, 67 dielectric fields, 69 acoustic fields, 71 and magnetic force 73 .…”
Section: Advanced Technologies For Isolating and Releasing Ctcsmentioning
confidence: 99%
See 1 more Smart Citation